2014
DOI: 10.1111/1753-0407.12120
|View full text |Cite
|
Sign up to set email alerts
|

Progression from impaired fasting glucose to type 2 diabetes mellitus among Chinese subjects with and without hypertension in a primary care setting 在中国初级保健机构中合并以及不合并高血压的受试者从空腹血糖受损进展到2型糖尿病的调查

Abstract: Overall, more than one-fifth of IFG subjects in the primary care setting developed T2DM within 5 years. Health care professionals can target interventions to patients with risk factors for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to report on progression rates from NGT, isolated IFG, isolated IGT, or combined IFG/IGT with or without HTN in a high risk population without T2D in Iran. In contrast to the findings of two other studies, we showed concomitant HTN did not appear to be a more robust predictor of progression to T2D [5,6]. Estimates of progression to diabetes will depend upon the methodological factors, the definition of the isolated IFG, isolated IGT, and combined IFG/IGT and diabetes used, unknown time spent with isolated IFG, isolated IGT, and pre-diabetes, sample size, and the composition of the community examined by age and gender, making comparisons between studies of limited values.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first study to report on progression rates from NGT, isolated IFG, isolated IGT, or combined IFG/IGT with or without HTN in a high risk population without T2D in Iran. In contrast to the findings of two other studies, we showed concomitant HTN did not appear to be a more robust predictor of progression to T2D [5,6]. Estimates of progression to diabetes will depend upon the methodological factors, the definition of the isolated IFG, isolated IGT, and combined IFG/IGT and diabetes used, unknown time spent with isolated IFG, isolated IGT, and pre-diabetes, sample size, and the composition of the community examined by age and gender, making comparisons between studies of limited values.…”
Section: Discussioncontrasting
confidence: 99%
“…Estimates of progression to diabetes will depend upon the methodological factors, the definition of the isolated IFG, isolated IGT, and combined IFG/IGT and diabetes used, unknown time spent with isolated IFG, isolated IGT, and pre-diabetes, sample size, and the composition of the community examined by age and gender, making comparisons between studies of limited values. Fu et al [5] reported that IFG predicted the development of T2D with an incidence rate of 0.047 in hypertensive individuals and 0.031 in non-hypertensive individuals in a Hong Kong Chinese primary care setting. In a large national managed care claims database, Francis et al [6] examined the healthcare utilization and cost burden of patients with pre-diabetes, with and without co-morbid HTN, who progressed to T2D.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations